2019
DOI: 10.3892/ol.2019.10367
|View full text |Cite
|
Sign up to set email alerts
|

Management of mandibular odontogenic keratocyst through radical resection: Report of 35 cases

Abstract: The present study reported the clinical outcomes of 35 patients with mandibular odontogenic keratocysts (OKCs) following treatment by radical resection and immediate defect reconstruction. Amongst 565 patients with OKCs that were treated between April 2003 and May 2015, 35 patients underwent segmental or marginal mandibulectomy. The use of radical resection was based on clinical and/or radiographic evidence of size, cortical perforation and subsequent soft tissue involvement, and on the history of previous rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Many studies showed the lowest recurrence rates with aggressive resection, but at the cost of high morbidity, increased risk of local complications, such as pathologic bone fractures, and reduced quality of life [4,13]. Therefore, some authors criticize this approach and point out that epithelial residues or microcysts may persist at soft tissue extensions [14]. Enucleation is the treatment of choice because of its lower recurrence rate and conservative technique [12].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed the lowest recurrence rates with aggressive resection, but at the cost of high morbidity, increased risk of local complications, such as pathologic bone fractures, and reduced quality of life [4,13]. Therefore, some authors criticize this approach and point out that epithelial residues or microcysts may persist at soft tissue extensions [14]. Enucleation is the treatment of choice because of its lower recurrence rate and conservative technique [12].…”
Section: Discussionmentioning
confidence: 99%
“…The conservative treatment by enucleation can be sufficient for particular OKCs, with or without any adjuvant application of Carnoy’s solution [ 19 , 20 ]. Moreover, our patient was young, and, in general, a more radical treatment of the lesion could reduce the quality of life by increasing morbidity and risk of local complication (eg, pathological bone fracture) [ 21 , 22 ]. Pereira Santana et al used the same protocol in a similar posterior mandible lesion.…”
Section: Discussionmentioning
confidence: 99%
“…When OKCs originate in the mandible, the most common location is the posterior sextant, the angle or the ramus (4,5). Cases of OKCs often progress to the condyle because of their aggressive nature (6,7); however, to the best of our knowledge, only two reports of OKCs in the condyloid process that are not continuous with the surrounding areas have been reported (8,9). In both cases, OKCs occurred in the condylar head, which was resected.…”
Section: Introductionmentioning
confidence: 99%